Artificial Intelligence and Well-Being: Voices from Academic Writing Lecturers - Hikmah, Durratul; Hasanah, Roviatul (Universitas Nurul Jadid, 2025)
This study aims to explore the impact of artificial intelligence (AI) integration on the professional identity and well-being of lecturers teaching academic writing in higher education. Employing a qualitative phenomenological approach, the study involved three lecturers from different institutions in East Java. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that lecturers respond to AI integration adaptively and reflectively. Rather than rejecting the use of AI tools such as ChatGPT or Grammarly, they selectively incorporate them into their teaching practices to support idea generation and increase task efficiency. However, they also express concerns regarding the authenticity of student writing and the shifting nature of their pedagogical roles. Second, the study also finds that lecturers undergo an ongoing negotiation of their professional identities. They reconceptualize their roles not merely as technical instructors but as facilitators of digital literacy and academic ethics. In doing so, they strive to uphold professional values, despite facing institutional and collegial pressures. Moreover, exposure to AI has an ambivalent effect on lecturers' well-being. While it generates anxiety and social disconnection, it also stimulates renewed motivation and creativity in teaching. This study highlights the importance of institutional support and reflective spaces that enable educators to.